Pharmacokinetic properties, in vitro metabolism and plasma protein binding of govaniadine an alkaloid isolated from Corydalis govaniana Wall - Marques, Lucas M. M.; Callejon, Daniel R.; Pinto, Larissa G.; Campos, Michel L. de [UNESP]; Oliveira, Anderson R. M. de; Vessecchi, Ricardo; Adhikari, Achyut; Shrestha, Ram L. S.; Peccinini, Rosangela G. [UNESP]; Lopes, Norberto P. (Elsevier B.V., 2016)
Govaniadine (GOV) is an alkaloid isolated from Corydalis govaniana Wall. It has been reported to show a different number of biological activities including anti-urease, leishmanicidal and antinociceptive. The present study aims to characterize the GOV in vitro metabolism after incubation with rat and human liver microsomes (RLM and HLM, respectively) and to evaluate its pharmacokinetic properties. The identification of GOV metabolites was conducted by different mass analyzers: a micrOTOF II-ESI-ToF Bruker Daltonics (R) and an amaZon-SLion trap (IT) Bruker Daltonics (R). For the pharmacokinetic study of GOV in rats after intravenous administration, a LC-MS/MS method was developed and applied to. The analyses were performed using an Acquity UPLC (R) coupled to an AcquityTQD detector equipped with an ESI interface. The liver microsomal incubation resulted in new O-demethylated, di-hydroxylated and mono-hydroxylated compounds. Regarding the method validation, the calibration curve was linear over the concentration range of 2.5-3150.0 ng mL(-1), with a lower limit of quantitation (LLOQ) of 2.5 ng mL(-1). This method was successfully applied to a pharmacokinetic study. The profile was best fitted to a two-compartment model, the first phase with a high distribution rate constant (alpha) 0.139 +/- 0.086 min(-1), reflected by the short distribution half-life (t1/2 alpha) 9.2 +/- 8.9 min and the later one, with an elimination half-life (t1/2 beta) 55.1 +/- 37.9 min. The main plasma protein binding was 96.1%. This is a first report in this field and it will be useful for further development of govaniadine as a drug candidate. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Govaniadine; in vitro metabolism; Pharmacokinetics; Two-compartment model